Pelatihan Budidaya Sayuran Secara Vertikultur di Pekarangan Guna Ketahanan Pangan Rumah Tangga - Endah Djuwendah; Tuti Karyani; Zumi Saidah; O Hasbiansyah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
One of the efforts to increase food sufficiency, resilience and self-sufficiency is the use of the yard. Cultivation of vegetables using verticulture techniques can be applied in the use of yards. The verticulture technique was chosen because it has advantages: it does not require large costs, is easy, can be a source of family food, the beauty of the home and the environment and produces oxygen. This training activity aims to introduce vegetable farming techniques with the verticulture system as an effort to strengthen household food security. Participants in the activity were members of the Kencana Lestari Women's Farmer Group, Rancaekek Kencana Village, Bandung Regency. The methods used in this activity are lectures, practice and mentoring. The methods used in this activity are lectures, practice and mentoring.This activity has provided benefits for activity participants. The result was that there was a significant change in cognitive terms, namely an increase in the level of participants' knowledge about vegetable cultivation techniques using the verticulture system. For the psychomotor aspect, there is an increase in the skills of participants to cultivate various types of vegetable plants using verticulture techniques.